2014
DOI: 10.1088/0004-637x/791/2/120
|View full text |Cite
|
Sign up to set email alerts
|

Multiple and Fast: The Accretion of Ordinary Chondrite Parent Bodies

Abstract: Although petrologic, chemical, and isotopic studies of ordinary chondrites and meteorites in general have largely helped establish a chronology of the earliest events of planetesimal formation and their evolution, there are several questions that cannot be resolved via laboratory measurements and/or experiments alone. Here, we propose the rationale for several new constraints on the formation and evolution of ordinary chondrite parent bodies (and, by extension, most planetesimals) from newly available spectral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
125
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(142 citation statements)
references
References 121 publications
13
125
4
Order By: Relevance
“…It was further proposed that Hebe could be the parent body of an ancient asteroid family (Gaffey & Fieber-Beyer, 2013). The idea of H chondrites mainly originating from Hebe, however, was recently weakened by the discovery of a large number of asteroids (including several asteroid families) with similar spectral properties (hence composition, Vernazza et al, 2014). Here, we challenge this hypothesis by studying the three-dimensional shape and topography of Hebe derived from disk-resolved observations.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It was further proposed that Hebe could be the parent body of an ancient asteroid family (Gaffey & Fieber-Beyer, 2013). The idea of H chondrites mainly originating from Hebe, however, was recently weakened by the discovery of a large number of asteroids (including several asteroid families) with similar spectral properties (hence composition, Vernazza et al, 2014). Here, we challenge this hypothesis by studying the three-dimensional shape and topography of Hebe derived from disk-resolved observations.…”
Section: Introductionmentioning
confidence: 92%
“…For comparison, the five known S-type families spectrally analogous to Hebe (therefore to H chondrites; Vernazza et al 2014) and located close to the main-belt 3:1 and 5:2 mean-motion resonances, namely Agnia (located at semi-major axis a=2.78 AU and eccentricity e=0.09), Koronis (a=2.87 AU, e=0.05), Maria (a=2.55 AU, e=0.06), Massalia (a=2.41 AU, e=0.14) and Merxia (a=2.75 AU, e=0.13) encompass a total volume of respectively ∼ 2.4 × 10 4 km 3 , 5.6 × 10 5 km 3 , 3.6 × 10 5 km 3 , 5.7 × 10 4 km 3 and 1.8 × 10 4 km 3 when the larger member of each family is removed. Family membership was determined using Nesvorný (2015)'s Hierarchical Clustering Method (HCM)-based classification (http://sbn.psi.edu/pds/resource/nesvornyfam.html) and rejecting possible interlopers that do not fit the "V-shape" criterion as defined in Nesvorný et al (2015).…”
Section: Topographymentioning
confidence: 99%
“…Gefion is the only known family with large members of L (as opposed to H and LL) chondrite composition (Vernazza et al. ) and some asteroids found in the 3:1 mean‐motion resonance, e.g., (355) Gabriella, (14470) Utra, and (1722) Goffin, have L chondrite‐like spectra (Fieber‐Beyer and Gaffey ). In more recent years, however, the reflection spectra of some Gefion family members were found to resemble that of H chondrites and basaltic achondrites (McGraw et al.…”
Section: Introductionmentioning
confidence: 99%
“…This small subset of H-chondrite like asteroids were suggested as a possible old, dispersed asteroid family belonging to (6) Hebe (Gaffey and Fieber-Beyer, 2013). Complementing the existing and ever growing list of H-chondrite candidates near the 3:1 Kirkwood Gap, Vernazza et al (2014) identified several additional asteroids as viable H-chondrite candidates. Furthermore, Burbine et al (2002) make the point that there may be several H chondrite asteroids from the original parent body.…”
Section: Discussionmentioning
confidence: 94%
“…It is probable that the H-chondrites and IIE irons came from (6) Hebe (Gaffey and Gilbert, 1998), though caveats exist (e.g., Rubin and Bottke, 2009). The identification of many more large asteroids with H chondrite-like spectra also means that more candidates are now available to serve as a source for these meteorites (Vernazza et al, 2014).…”
Section: Introductionmentioning
confidence: 99%